Research on hierarchical control algorithm for SMES-BESS hybrid energy storage system based on multilevel power allocation - Liu, Haiyang; Li, Jun; Wang, Pengfei; He, Baocan; Lu, Jing; Wu, Yanan; Tian, Yunxiang; Mao, Huafeng; Sun, Hanbin (Proceedings of SPIE, the international society for optical engineering, 2025)
The superconducting magnetic energy storage (SMES) system has high power density and zero resistance characteristics, and has great potential for future development. This study proposes a hybrid energy storage system (HESS) that combines SMES with an electrochemical energy storage system (BESS) to enhance the short-term power support performance of electrochemical energy storage, introduces empirical mode dynamics (EMD) and decomposes multi-level power distribution methods, optimizes HESS internal power distribution and energy storage unit state of charge (SOC) management, and realizes SMES and BESS power and energy hierarchical complementary regulation. The feasibility and effectiveness of the research algorithm were verified by MATLAB/Simulink. Taking the power fluctuation of a wind farm as an example, its feasibility was verified, showing its great potential in other application scenarios.